God of the Rich and God of the Poor - Mataragnon, Rita H (Journal of Dharma, 1984)
Is the God of the rich the same God as the God of the poor? Do the rich and the poor see the same images and qualities of God? Do they worship God and express their religiosity in the same way? Do they perceive their lives to be controlled to the same extent by God?